ANALISIS KEPUASAN KONSUMEN BERBELANJA BUAH DI PASAR MODERN SAAT PANDEMI COVID-19 DI KOTA PEKANBARU (STUDI KASUS JUMBO MART DELIMA) - Jannah, Yasmin Raudhatul; Edwina, Susy; Rifai, Ahmad (Universitas Sebelas Maret, 2023)
Jumbo Mart Delima is a modern market that sells various types of imported and local fruits. During the Covid-19 pandemic, people tend to choose to shop in places that are strict in implementing health protocols such as modern markets because they feel more secure when shopping. This research aims to identify the characteristics and analyze consumer satisfaction in shopping for fruit in modern markets during the Covid-19 pandemic. This research was conducted at the modern market of JMD in Delima Village, Tampan District, Pekanbaru city, with a survey method in June - July 2021. The selected respondents were consumers who came to shop for fruit at JMD with a purposive sampling method where the number of samples was 50 respondents. The data analysis method used is the Customer Satisfaction Index (CSI) method to determine customer satisfaction and the Importance Performance Analysis (IPA) method to identify the level of importance attribute and priority improvements that JMD must make. The results showed that the CSI value was 85.85%, which means that consumers are very satisfied with the performance of JMD. The highest CSI value is in cost and convenience at 89.91%. Based on the IPA method, there is one variable in quadrant I (main priority), five variables in quadrant II (maintain achievement), and one variable in quadrant III (low priority). The IPA results on attributes are known to have no attributes in quadrant I, there are 16 attributes in quadrant II, eight attributes in quadrant III, and three attributes in quadrant IV.